Nationwide and long-term epidemiological research of snakebite envenomation in Taiwan during 2002-2014 based on the use of snake antivenoms: A study utilizing National Health Insurance Database - Jen-Yu Hsu; Shu-O Chiang; Chen-Chang Yang; Tan-Wen Hsieh; Chi-Jung Chung; Yan-Chiao Mao (Public Library of Science (PLoS), 2023)
Introduction In Taiwan, six venomous snake species with medical importance have been found; however, long-term epidemiological data of snakebite envenomation (SBE) is lacking. This study aimed to explore the epidemiology of SBE based on the distribution and use of different antivenoms in different parts of Taiwan to facilitate the development of prevention strategies and resource allocation. Methods and results This retrospective study was conducted using the Taiwan National Health Insurance Research Database from 2002 to 2014. A total of 12,542 patients were treated with antivenoms. The directly standardized cumulative incidence was 3.6 cases per 100,000 individuals based on the 2000 World Standard Population. The incidence of SBEs peaked in the summer (35.9%). The relative risk (RR) of male patients versus female patients was 2.5 (p < 0.0001). The RRs of patients aged 18-64 and ≥65 years versus those aged <18 years were 6.0 (p < 0.0001) and 14.3 (p < 0.0001), respectively. Furthermore, the RR of eastern Taiwan versus northern Taiwan was 6.8 (p < 0.0001). The RR of agricultural workers versus laborers was 5.5 (p < 0.0001). Compared with patients envenomed by Trimeresurus stejnegeri stejnegeri or Protobothrops mucrosquamatus, those envenomed by Naja atra or Bungarus multicinctus multicinctus were more likely to occur in central (adjusted odds ratio [aOR] = 2.6, p < 0.0001) or southern (aOR = 3.2, p < 0.0001) Taiwan, but less frequently among agricultural workers (aOR = 0.6, p < 0.0001). The overall case-fatality rate was 0.11%. Conclusions Among Asian countries, Taiwan had low incidence and case-fatality rates of SBE. Risk factors included male gender, old age, summer season, being in eastern Taiwan, and being an agricultural worker. Differences of the epidemiological findings between snake species should be focused on when developing strategies for snakebite prevention. Author summary SBE is a neglected tropical disease of highest priority to be aware of, and its epidemiology varies widely worldwide. This study explored the nationwide and long-term epidemiology of SBE based on the use of snake antivenom in Taiwan, including its incidence, risk factors, complications, and management. This could facilitate the development of preventive strategies and resource allocation. In Taiwan, six medically important venomous snake species were found; however, majority (73.3%) of the envenomation events were associated with T. s. stejnegeri (bamboo pit viper) and P. mucrosquamatus (Taiwan habu) and some (17.1%) with N. atra (Chinese cobra) and B. m. multicinctus (many-banded krait). The risks varied depending on the season, sex, age, geographic region, and occupation. Compared with patients envenomed by crotalines, those envenomed by elapids were more likely to undergo surgery due to serious wound complications caused by N. atra or endotracheal intubation due to respiratory failure caused by B. m. multicinctus. The low case-fatality rate observed might be due to easy access to modern medicine, immediate availability of antivenoms in healthcare facilities, few adverse effects of antivenoms, and prompt surgical intervention. The lack of highly venomous snakes with highly potent venom is a leading factor in low case fatality.